2022
DOI: 10.3390/biom12081037
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Induced by Endoplasmic Reticulum Stress Regulates Cumulus-Oocyte Complex Expansion in Polycystic Ovary Syndrome

Abstract: Endoplasmic reticulum (ER) stress activated in granulosa cells contributes to the pathophysiology of polycystic ovary syndrome (PCOS). In addition, recent studies have demonstrated that Notch signaling plays multiple roles in the ovary via cell-to-cell interactions. We hypothesized that ER stress activated in granulosa cells of antral follicles in PCOS induces Notch signaling in these cells, and that activated Notch signaling induces aberrant cumulus-oocyte complex (COC) expansion. Expression of Notch2 and Not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…70 The ovarian morphology of patients with PCOS is characterized as PCOM with interstitial fibrosis. 71 We demonstrated that ER stress contributes to the pathophysiology of PCOS through multiple functional alterations in granulosa cells 48,52,53,[72][73][74] (Figure 3). ER stress stimulates the production of transforming growth factor-β1 (TGF-β1), a profibrotic growth factor, in granulosa cells and accelerates interstitial fibrosis in the ovary, which is a characteristic of PCOS.…”
Section: Er Stress In Pcosmentioning
confidence: 94%
See 2 more Smart Citations
“…70 The ovarian morphology of patients with PCOS is characterized as PCOM with interstitial fibrosis. 71 We demonstrated that ER stress contributes to the pathophysiology of PCOS through multiple functional alterations in granulosa cells 48,52,53,[72][73][74] (Figure 3). ER stress stimulates the production of transforming growth factor-β1 (TGF-β1), a profibrotic growth factor, in granulosa cells and accelerates interstitial fibrosis in the ovary, which is a characteristic of PCOS.…”
Section: Er Stress In Pcosmentioning
confidence: 94%
“… 76 Measurement of the diameters of COCs showed that the ER stress‐Notch pathway increases the size of COCs, although it remains to be determined whether such hypermaturity of COCs plays a causative role in the ovulatory dysfunction that characterizes PCOS. 74 …”
Section: Role Of Follicular Er Stress In the Patho...mentioning
confidence: 99%
See 1 more Smart Citation
“…Notch signaling in the follicular microenvironment also regulates ovarian development, including follicular assembly and growth, steroidogenesis, and angiogenesis ( 34 , 96 , 97 ). Notch signaling is activated in the GCs of patients and mice with PCOS ( 98 ). The UPR activates Notch signaling followed by the induction of some ovulation-related genes in cultured human GCs.…”
Section: Pathophysiological Role Of Er Stress In Pcosmentioning
confidence: 99%
“…A common and highly conserved signal transduction pathway that is activated via direct cell-to-cell contacts is the NOTCH signal pathway. It has already been shown in mammalian ovaries [4,5] that this pathway is important for the recruitment of primordial follicles [6,7] during folliculogenesis [8], as well as for oocyte development and the proliferation and function of granulosa cells [9][10][11][12]. The expression of the components of this signaling pathway is highly dynamic and, among others, depends on the oestrous cycle [13].…”
Section: Introductionmentioning
confidence: 99%